For Our Soul : Ethiopian Jews in Israel - Wagaw, Teshome G., 1930- (Book collections on Project MUSE., 2018)
Between 1977 and 1992, practically all Ethiopian Jews migrated to Israel. This mass move followed the 1974 revolution in Ethiopia and its ensuing economic and political upheavals, compounded by the brutality of the military regime and the willingness⁰́₄after years of refusal⁰́₄of the Israeli government to receive them as bona fide Jews entitled to immigrate to that country. As the sole Jewish community from sub-Sahara Africa in Israel, the Ethiopian Jews have met with unique difficulties. Based on fieldwork conducted over several years, For Our Soul describes the ongoing process of adjustment and absorption that the Ethiopian Jewish immigrants, also known as Falasha or Beta Israel, experienced in Israel.